Determining the necessity of phenyl ring π-character in warfarin. Issue 15 (1st August 2019) - Xing, Hui; Houston, Sevan D.; Chen, Xuejie; Jin, Da-Yun; Savage, G. Paul; Tie, Jian-Ke; Williams, Craig M.
Graphical abstract: Abstract: Despite the difficulty in administering a safe dose regimen and reports of emerging resistance, warfarin (1 ) remains the most widely-used oral anticoagulant for the prevention and treatment of thrombosis in humans globally. Systematic substitution of the warfarin phenyl ring with either 1, 3, 5, 7-cyclooctatetraene (COT) (2 ), cubane (3 ), cyclohexane (4 ) or cyclooctane (5 ) and subsequent evaluation against the target enzyme, vitamin K epoxide reductase (VKOR), facilitated interrogation of both steric and electronic properties of the phenyl pharmacophore. The tolerance of VKOR to further functional group modification (carboxylate 14, PTAD adduct 15 ) was also investigated. The results demonstrate the importance of both annulene conferred π-interactions and ring size in the activity of warfarin.